How is it done? (London Reader's Digest, 1992)
Fascinating inside stories behind the marvels of human ingenuity-from weapons fashioned by the first hunters to medical miracles of the modern age.
Include Colored Illustration, Indexes
Keywords: Science -- Technological innovations -- Technology